Health-related quality of life in metastatic and adjuvant breast cancer patients = Gesundheitsbezogene Lebensqualität bei Brustkrebspatientinnen in der metastasierten oder adjuvanten Situation - Wallwiener, Markus (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: When cancer patients have advanced disease and a primary cure is no longer possible, the focus is on maintaining the patientʼs quality of life. Recent therapeutic advances in breast cancer treatment mean that even patients with metastatic disease can remain stable for long periods of time. The aim of this study was to look at the health-related quality of life (HRQL) of these patients and compare it with data for the general population and to show the differences in outcomes for different survey instruments used to measure quality of life. Material and Methods: A total of 96 breast cancer patients with metastatic disesae or receiving adjuvant therapy were questioned about their quality of life. Patients were investigated using the established survey instruments EORTC QLQ-C30, EORTC QLQ-BR23, EQ-5D-5L and EQ VAS. All patients filled out questionnaires. Statistical analysis was done using MS Excel and SPSS. Results: Although the questionnaires were completed at the same time, the different questionnaires showed significant differences with regard to the level of stress experienced by the patient. When the EQ VAS questionnaire was used, the patientʼs current state of health was assessed as significantly better than with the EORTC QLQ-C30. Overall, all aspects of patientsʼ quality of life were found to be in need of optimization and HRQL of patients was significantly poorer in all areas compared to the reference population. Conclusion: To improve the quality of life of patients with metastatic disease, it is necessary to continuously monitor the success of therapy. The choice of survey tools is highly relevant as assessments differ considerably depending on the choice of questionnaire.